2013
DOI: 10.1117/12.2019110
|View full text |Cite
|
Sign up to set email alerts
|

Chaos and entanglement in atomic systems interacting with photons

Abstract: The influence of chaotic behavior of coherent state (CS) parameters on entanglement dynamics in system of two level atoms and photons in cavity is investigated. The initial state of the system is chosen as factorized production of photon and atomic coherent states. To find a solution of the Schrödinger equation, we presented the time-dependent wave function in the form of a wave packet in CS representation. The phase portraits and Poincare sections for classical dynamics of CS were computed, and time dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Among the phenomena recently theoretically studied theoretically it is worth mentioning the effect of dipole-dipole interaction on the quantum entanglement measure 13,14 and the influence of chaotic behavior of coherent state parameters on the entanglement dynamics in a system of two-level atoms and photons in a cavity. 15 The simplest model system relevant to quantum entanglement in quantum data processing systems is a pair of cubits, i.e., two identical two-level quantum objects. Recently 16 it was demonstrated that the presence of high intensity laser field can generate a high degree of entanglement in this system.…”
Section: Introductionmentioning
confidence: 99%
“…Among the phenomena recently theoretically studied theoretically it is worth mentioning the effect of dipole-dipole interaction on the quantum entanglement measure 13,14 and the influence of chaotic behavior of coherent state parameters on the entanglement dynamics in a system of two-level atoms and photons in a cavity. 15 The simplest model system relevant to quantum entanglement in quantum data processing systems is a pair of cubits, i.e., two identical two-level quantum objects. Recently 16 it was demonstrated that the presence of high intensity laser field can generate a high degree of entanglement in this system.…”
Section: Introductionmentioning
confidence: 99%